Approaches to synthesis of ([1,2,4]triazolo[1,5-c]quinazolin-2-yl)benzoic acids as potential anti-inflammators - Krasovska, N. I.; Красовська, Наталя Ігорівна (My University, 2022)
Non-steroidal anti-inflammatory drugs (NSAIDs) are a common and diverse group of compounds that are mainly used to treat patients suffering from pain and inflammation (chronic pain, osteoarthritis, rheumatoid arthritis, postoperative surgical conditions, etc.) [1, 2]. In addition, this group of drugs is used as analgesics and antipyretics. Aryl carboxylic acids and their derivatives, which were among the first to be introduced into medical practice, are still important among NSAIDs [3]. In addition to the well-known salicylic and acetylsalicylic acids, this group of anti-inflammatory agents includes salts of salicylic acid, salsalate and diflunisal. Recently, representatives of anthranilic (2-aminobenzoic) acid derivatives have also been widely used, namely fenamates (mefenamic, meclofenamic, flufenamic and tolfenamic acids).
Підходи до синтезу ([1,2,4]триазоло[1,5-c]хіназолін-2-іл)бензойних кислот як потенційних протизапальних агентів
https://orcid.org/0000-0001-5902-6596
Keywords: heterocyclization; oxidative cyclization; ([1,2,4]triazolo[1,5-c]-quіnazolin- 2-yl)benzoic acids; Dimroth rearrangement; spectral characteristics; anti-inflammatory activity; гетероциклізація; окиснювальна циклізація; ([1,2,4]триазоло[1,5-c] хіназолін-2-іл)бензойна кислота; перегрупування Дімрота; спектральні характеристики; протизапальна активність